Analysis Of Nursing Care In Chronic Kidney Disease Patients With Anxiety Through Combination Of General Therapy With Mindfulness Therapy In Pku Muhammadiyah Gombong Hospital - Misdiyanti, Desi; Sumarsih, Tri; Djalil, Abdul (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2022)
Chronic kidney disease (CKD) is a condition where there is progressive and irreversible renal function impairment. The main psychological problem that often occurs in patients with kidney failure undergoing hemodialysis is anxiety. The aim of this study was to describe the results of nursing care for chronic kidney disease (CKD) patients with anxiety nursing problems through combination generalist therapy with mindfulness therapy in PKU Muhammadiyah Gombong hospital. The method of this research was descriptive with a case study approach in the form of nursing care for 5 chronic kidney disease patients who experience anxiety with a duration of approximately 20 minutes at each meeting, starting from assessment, diagnosis, intervention, implementation, and evaluation. The instruments used are psychosocial mental nursing care format, observation sheet, sign and symptom format, and standard operating procedures for mental nursing actions and HADS (Hospital Anxiety and Depression Scale). The results of this case study showed that before the nursing implementation, all patients (5 patients) had experienced signs and symptoms of anxiety. After being given a combination of generalist therapy (deep breath relaxation technique, five finger hypnosis and spiritual technique) with mindfulness therapy, all patients experienced a decrease in signs and symptoms of anxiety as well as an increase in the patient's ability to control anxiety. The most significant decrease in signs and symptoms of anxiety in the fourth patient was a decrease of 6 signs and symptoms (62%). The results of the measurement with the HARS instrument, the patient's level of anxiety before the intervention was given the majority of patients experienced moderate anxiety (60%), while after the intervention, the majority of patients experienced mild anxiety (60%). Meanwhile, the ability of the five patients to reduce anxiety increased from a score of 7 (60%) to a score of 21 (100%). Individual therapy using generalist therapy combined with mindfulness therapy is recommended to be applied by nurses in providing psychosocial psychiatric nursing care